A case of polymicrobial anaerobic spondylodiscitis due to Parvimonas micra and Fusobacterium nucleatum. (26th April 2017) - Cleaver, Leanne M; Palanivel, Shara; Mack, Damien; Warren, Simon
Abstract : Introduction. Here, we present a case of polymicrobial anaerobic spondylodiscitis. Case Presentation. A forty-five year-old female patient was referred to a specialist orthopaedic hospital with an eight week history of back pain without fevers. X-ray imaging and magnetic resonance imaging showed acute osteomyelitis of the twelfth thoracic and first lumbar vertebrae. Prolonged enrichment cultures grew Parvimonas micra and Fusobacterium nucleatum, identified by matrix-assisted laser desorption ionisation-time of flight (MALDI-ToF) mass spectrometry (MS). The patient was successfully treated with six weeks of intravenous ertapenem and oral clindamycin. Conclusion. Anaerobic discitis is rare, and polymicrobial discitis is rarer still. A PubMed literature review revealed only seven cases of F. nucleatum discitis and only twelve cases of P. micra discitis; this includes only one other reported case of a polymicrobial discitis due to infection with both anaerobes. We emphasise the importance of prolonging enrichment culture and the use of fast yet accurate identification of anaerobes using MALDI-ToF MS in these infections.